Flying Over the World of Birds: A Teaching and Bird Conservation Strategy (2017)
This paper provides introductory information for those wishing to start in the development of educational projects using the birds as a tool to educate, directed, especially, for those who care about biodiversity, birds and conservation. Birds are a diverse group of vertebrates, and an important resource in biology teaching. This paper shows the work of teaching practice developed within the curriculum of Bachelor’s Degree of Biology at Universidad Pedagógica Nacional, held during the periods 2013-II and 2014-I, which was aimed to ninth grade students from Emilio Valenzuela school. The aim of this work was to create a learning, reflection and motivation space towards the protection and consolidation of values around biodiversity; also, using binoculars, ICT (including videos, audios and recordings), notebook and field diary an approaching of students toward the birds for their study and conservation was promoted through the Teaching Ecology from the School Yard (EEPE, for its acronym in Spanish).